(3GdSdhc GdJfXjej aj efXeGJ GdCYeGd (B/s - (3GdYejGf, eMehO SdeGfs ((3YeGf(B: s (3OGQ hGFd ddWHGYI hGdfTQ(B, s, 2002)
(3eaghe GdSdhc GdJfXjej,GdfXQjGJ GdGOGQjI hGdSdhc GdJfXjej,GdEOQGc,GdEJLGgGJ,Gdbje,GdTNUjI,GdJYde,VZhW GdYed,GdEMHGW,GdSdhe GdLeGYj aj GdefXeGJ,Gdgjcd GdJfXjej,GdEJUGd,GdbjGOI,GdOGaYjI hGdMaR GdEfSGfj,GdefGN GdJfXjej hGdKbGaI GdJfXjejI,GdHjFI GdJfXjejI,GdJZjjQ hGdJWhjQ GdJfXjej,GdUQGY GdJfXjej,GdGHOGY GdJfXjej,eSJbHd GdSdhc GdJfXjejs
(3HjHdjhZQGajG U(B.411s
Keywords: (3GdGOGQI(B- (3JfXje s; (3efXeGJs